ChemInform Abstract: Alkali Metals Extraction Reactions with the Silicides Li15Si4 and Li3NaSi6: Amorphous Si versus allo‐Si. Issue 5 (February 2015) - Zeilinger, Michael; Jantke, Laura‐Alice; Scherf, Lavinia M.; Kiefer, Florian J.; Neubueser, Gero; Kienle, Lorenz; Karttunen, Antti J.; Konar, Sumit; Haeussermann, Ulrich; Faessler, Thomas F.
Abstract Alkali metal extraction reactions with Li15Si4 (liq.